Singapore's move towards a cashless society - Lee, Ling Nyee (2015)
Many articles have been written on the popularity of the cashless payment system in Singapore. More and more people are using the cashless mode of payment such as credit cards, charge cards, NETS, cheques and GIRO. This paper explains the various modes of payment available in Singapore, the issues and problems involved with regards to NETS and credit cards, and assess the possibility of Singapore moving towards a totally cashless society. A survey was conducted in five of the most populated areas to find out the payment pattern of the general public. The results of the survey show that there is a distinct difference between the mode of payment used to settle government bills and private sector bills. Though the majority of the respondents use the cashless mode of payment like GIRO and/or cheques to settle their government bills, there is still a great percentage of people using cash to settle their bills. To encourage these people to switch from cash payments to GIRO, the government could consider giving rebate to GIRO users. Most of the respondents use both cash and cashless mode of payment to settle their purchases of goods and services from private sector as they find both payment methods equally important and indispensable. Singapore is unlikely to become a totally cashless society in the very near future. Much effort are required from both the government and the general public. The various government bodies need to put in more effort and incentive to encourage the use of cashless mode of payment while the attitude of the general public towards the use of cashless payment methods also has to be changed to achieve a totally cashless society in Singapore.